ANALISIS USAHA TANI PADI (Oriza sativa L) DENGAN SISTEM JAJAR LEGOWO 2:1 DI KELURAHAN BINUANG KECAMATAN BINUANG KABUPATEN TAPIN PROVINSI KALIMANTAN SELATAN - Susmawati Susmawati (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2018)
The study aims:1. To determine the cost of farming system rice 2. To determine income of farming system rice 3. To determine whether the farm is worth it or not.  This result was conducted in the experimintal Land Own  for 4 months from May until the month of August 2016. Analysis of data used in this study :1). Analysis BEP Volume Production 2.)Analysis BEP Production Price 3.)Analysis B/C ratio 4.) Analysis of ROI. Production volume analysis result show 1904,2 kg, the analysis results BEP price production show Rp. 3.115,51;the analysis results B/C ratio 1,60 show that the farm should be develoved rice, whereas the analysis results show 60,48 % ROI. The results of analysis of total cost production Rp.11.901.250, while the results of the analysis of the total revenue Rp.19.100.000;the results of cost analysis show profit each harvest of Rp.7.198.750